A Systematics Review on the Impact of Emergency Supply Chain Management, Operational Efficiency, and Supply Chain Traceability on Public Health - Akubia, Gilbert Korku; Gaffar, Vanessa; Andriana, Denny (Image : Jurnal Riset Manajemen, 2024)
This systematic review aims to explore and analyze the intricate of Emergency Supply Chain Management (ESCM), Operational Efficiency (OE), and operational efficiency, and supply chain traceability (SCT) in ensuring public health during crises. The study systematically reviews and synthesizes relevant literature from Scopus, Web of Science, Emerald, and Elsevier, employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. A comprehensive search across databases yielded 3,755 articles, from which 57 articles were selected for detailed analysis based on inclusion and exclusion criteria. The selected articles were critically assessed for their contribution to understanding the impact of Emergency Supply Chain Management, operational efficiency, and supply chain traceability impact on public health outcomes. The systematic review reveals key insights into the multifaceted influence of ESCM, OE and traceability on public health. Findings encompass the adoption of advanced technologies, such as RFID and blockchain, to enhance traceability in medical supply chains. operational efficiency, providing information on how coordinated procedures and wise resource distribution support the prompt and efficient provision of medical resources in both emergency scenarios and regular business operations. Managerial initiatives and standardized policies emerge as pivotal factors in ensuring efficient public health logistics. Collaboration between non-governmental organizations (NGOs) and government agencies plays a crucial role in mitigating challenges and optimizing public health.